2009
DOI: 10.1007/s10608-009-9241-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the Hopelessness Theory Account for Sex Differences in Depressive Symptoms Among Young Adults?

Abstract: The present study examined whether the sex difference in depression could be accounted for within the framework of the hopelessness theory of depression. Specifically, we tested whether young adults' negative inferential styles mediated the sex difference in depressive symptoms or whether sex moderated the cognitive vulnerability-stress effects on depressive symptoms in a multiwave longitudinal study. In doing so, we examined the different forms of negative inferential styles separately (causes, consequences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
3
17
0
1
Order By: Relevance
“…However, present findings show that the moderating role of age only appeared in boys (and thus depended on gender). These findings are partially consistent with studies supporting the cognitive vulnerability-stress model for boys only (Hankin et al 2001; Stone et al 2010). It is important to note that the prospective studies of Hankin et al and Stone et al were conducted with middle to late adolescents, whereas other studies that found support for the interaction only in girls examined younger samples (e.g., Abela and McGirr 2007).…”
Section: Discussionsupporting
confidence: 90%
“…However, present findings show that the moderating role of age only appeared in boys (and thus depended on gender). These findings are partially consistent with studies supporting the cognitive vulnerability-stress model for boys only (Hankin et al 2001; Stone et al 2010). It is important to note that the prospective studies of Hankin et al and Stone et al were conducted with middle to late adolescents, whereas other studies that found support for the interaction only in girls examined younger samples (e.g., Abela and McGirr 2007).…”
Section: Discussionsupporting
confidence: 90%
“…However, six of seven significant or marginally significant associations between parts of the inference style and the cognitive triad 4 weeks later are solely based on the female subsample. Although the sex differences are not consistent with Beck's cognitive theory (Beck, 1976, 1996) and the hopelessness model (Abramson et al, 1989), these results are consistent with previous empirical publications (Goldstein, 2006; Stone et al, 2010). Both studies found consistent associations between inference styles and depressive symptoms in female samples but not in male samples.…”
Section: Discussionsupporting
confidence: 64%
“…Research has indicated that women are about twice as likely to develop depression as men (Angst et al, 2002). However, while differences in cognitive variables between the sexes has been well studied (see for a review Nolen‐Hoeksema, 2006), there are only a few studies about possible differences in the associations between cognitive variables as proposed by Beck's cognitive theory Beck (1976, 1996) or the hopelessness model (Abramson et al, 1989) and depressive symptoms (Goldstein, 2006; Stone, Gibb, & Coles, 2010). Although neither of the two cognitive theories studied here predict sex differences in the associations between cognitive variables and depressive symptoms, both studies found that the association between stable and global attribution of negative events and depressive symptoms was significant in women but not in men.…”
mentioning
confidence: 99%
“…In the causal mediation component it is posited that hopelessness mediates between the diathesis-stress component and hopelessness depression symptoms in the etiological chain. Available evidence is inconsistent, with some researchers providing full or partial support for this hypothesis (e.g.. Hong, Gwee, & Karia, 2006) and others showing no support (e.g., Abela, 2001;Stone, Gibb, & Coles, 2010) Although much is known about the diathesis-stress component, only a few studies of the hopelessness theory have been carried out with undergraduate samples in China (e.g., Wang & Zhang, 2006;Xin, Ma, & Geng, 2006). Despite the strengths of these Chinese studies, Gibb and colleagues (2006) found some common limitations.…”
mentioning
confidence: 99%